Case report: Acne vulgaris treatment with 5-Aminolaevulinic acid photodynamic therapy and adalimumab: a novel approach - Ping, Yang; Jian Bo, Zhong; Xing Yun, Zhao; Ali, Kamran; Jun, Chen; Xu Lou, Inmaculada; Wu, Li Ming (Frontiers in Medicine, 2023)
Acne vulgaris is a common skin condition that affects a large proportion of teenagers and young adults. Despite the availability of various treatment options, many patients experience inadequate relief or intolerable side effects. Photodynamic therapy (PDT) is a growing interest in the treatment of acne vulgaris, with 5-Aminolaevulinic acid (ALA) being one of the most commonly used photosensitizers. Adalimumab is a biologic medication used to treat inflammatory skin conditions such as Psoriasis and Hidradenitis suppurativa (HS), which targets TNF-α. Combining different therapies, such as ALA-PDT and adalimumab, can often provide more effective and longer-lasting results. This report presents the case of a patient with severe and refractory acne vulgaris who was treated with a combination of ALA-PDT and adalimumab, resulting in significant improvement in the condition. The literature review highlights the significant comorbidity associated with acne, emphasizing the need for potential of TNF-α inhibitors for its effective treatments that address physical symptoms and ALA-PDT is known to treat scar hyperplasia, and to prevent or minimize the formation of post-acne hypertrophic scars. The combination of TNF inhibitors and ALA-PDT or adalimumab has shown promising results in treating inflammatory skin conditions, including severe and refractory acne vulgaris, as per recent studies.